Application of Black Cumin Oil (Nigella sativa) in Aquaculture: A Review of the Potential for Growth and Immunity Enhancement - Bagus Susilo; Fittrie Meyllianawaty Pratiwy; Iskandar Iskandar; Rafidah Othman; Roffi Grandiosa Herman (Jurnal Perikanan dan Kelautan, 2026)
Black cumin oil (Nigella sativa) is a natural ingredient that contains various bioactive compounds, including thymoquinone, flavonoids, and essential fatty acids, with antioxidant, anti-inflammatory, and immunostimulating effects. In the field of aquaculture, the use of black cumin oil as a feed supplement is being developed due to its potential in improve the growth performance and immune system of farmed fish. This article aims to systematically review research on the application of black cumin oil in aquaculture, focusing on improving fish growth rate and immune response. Based on a literature review, it was found that N. sativa supplementation in oil form in various fish species, such as Oncorhynchus mykiss, Clarias gariepinus, Oreochromis niloticus, and Anabas testudineus, was able to improve growth, feed conversion ratio, as well as immunological parameters such as phagocytic activity, immunoglobulin levels, and resistance to infection.